Strategi Bauran Pemasaran (Marketing Mix) 7p pada Ita Yunarta Organizer dalam Meningkatkan Jumlah Client Wedding Organizer - Romanika, Mita; Rusdiyanto Yuniardi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze how the 7P marketing mix strategy uses external & internal analysis of Ita Yunarta Organizer with the SWOT method to increase the number of Ita Yunarta clients to be superior to other wedding organizer service competitors. The research method used is descriptive, as part of qualitative analysis. Data were obtained through observation, documentation, and in-depth interviews related to the 7P marketing strategy (Product, Price, Place, Promotion, People, Process, & Physical) to evaluate strengths, weaknesses, opportunities, and threats with SWOT analysis. The results of this study were evaluated through IFAS (Internal Strategy Factor Analysis Summary) and EFAS (External Strategy Factor Analysis Summary) analysis. The results show internal strengths with a score of 2.859 and weaknesses with a score of 0.402, while external opportunities have a score of 3.008 and threats 0.496. The recommended strategy is SO, which focuses on utilizing internal strengths to pursue external opportunities.